Electrolyte additive, non-aqueous electrolyte and battery

By developing an electrolyte additive with high solubility, the additive decomposes in lithium batteries to produce SEI films, inhibits the generation of lithium dendrites, solves the problem of lithium dendrites affecting safety and stability in lithium batteries, and achieves the effect of improving the cycle stability of lithium batteries.

CN119542533APending Publication Date: 2025-02-28安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665846.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The growth of lithium dendrites in lithium batteries affects the safety and stability of the battery. The solubility of existing electrolyte additives such as lithium nitrate is limited, which limits its application.

Method used

An electrolyte additive is developed, which comprises a compound having a certain solubility, at least one substituent in the compound is a nitro group, which can decompose and produce a SEI film rich in LiNxOy and Li3N, inhibiting the production of lithium dendrites.

Benefits of technology

The electrolyte additive can effectively inhibit the production of lithium dendrites, improve the circulation stability and safety of lithium batteries, and at the same time has high solubility and compatibility, and can replace lithium nitrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542533A_ABST
    Figure CN119542533A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte additive which is characterized by comprising at least one of compounds shown in a formula I and a formula II: # imgabs0 #, in which R1 to R2 are at least one of hydrogen, nitryl, fluorine-containing groups, sulfur-containing groups, cyano groups, isocyano groups, alkenyl ester groups or alkyne ester groups, and R3 to R4 are at least one of hydrogen, nitryl, fluorine-containing groups, sulfur-containing groups, cyano groups, isocyano groups, alkenyl ester groups or alkyne ester groups; at least one substituent in the formula I is nitro, and at least one substituent in the formula II is nitro. The electrolyte additive disclosed by the invention has relatively high solubility, and can effectively inhibit the generation of lithium dendrites and improve the cycling stability of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to an electrolyte additive, a non-aqueous electrolyte and a battery. Background Art

[0002] Since the beginning of the 21st century, lithium batteries have developed rapidly. With the increase in consumer demand for electronic products, people have gradually put forward higher requirements for battery life. However, in the commercialization process, lithium dendrite growth has become one of the fundamental problems affecting the safety and stability of lithium batteries. Lithium nitrate (LiNO3), as a commonly used inorganic anion electrolyte additive, has been widely proven to effectively inhibit lithium dendrite growth, thereby improving the cycle stability and safety of lithium batteries, but the limited solubility of LiNO3 in the electrolyte limits its application.

[0003] Therefore, it is of great significance to develop an electrolyte additive with high solubility that can effectively inhibit the formation of lithium dendrites to improve the cycle stability of lithium batteries. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides an electrolyte additive, a non-aqueous electrolyte and a battery, wherein the electrolyte additive has high solubility, can effectively inhibit the generation of lithium dendrites, and improve the cycle stability of lithium batteries.

[0005] Therefore, in the first aspect of the present invention, the present invention provides an electrolyte additive, comprising at least one of the compounds represented by formula I and formula II:

[0006]

[0007] Among them, R 1~8 is at least one of hydrogen, nitro, fluorine-containing group, sulfur-containing group, cyano, isocyano, ene ester group or alkynyl ester group; at least one substituent in formula I is nitro, and at least one substituent in formula II is nitro.

[0008] The electrolyte additive of the present invention comprises at least one of the compounds shown in Formula I and Formula II. On the one hand, the compound has a certain solubility and can form an electrolyte with stable and uniform electrochemical properties; on the other hand, at least one substituent in the compound is a nitro group, which can decompose to produce a LiN-rich electrolyte. x O yThe SEI film of Li3N makes lithium deposition uniform, reduces the consumption rate of active lithium and electrolyte, inhibits the generation of lithium dendrites, and exerts the same technical effect as LiNO3. Other groups in the compound, such as fluorine-containing groups, sulfur-containing groups, cyano groups, isocyano groups, enester groups or alkynyl groups, help the electrolyte to form a solid electrolyte interface film (SEI film) rich in components. For example, compounds containing fluorine groups decompose to produce a SEI film rich in LiF; sulfur-containing groups have stronger reducing properties than carbonates (EC) on the negative electrode side due to the strong electronegativity of sulfur atoms, and can form a stable SEI film with excellent lithium ion conductivity at the interface better than solvents; compounds containing cyano and isocyano groups can remove water and hydrogen fluoride (HF) in the electrolyte, stabilize the electrolyte, and construct an SEI film containing N-based components; enester groups contain C=C double bond functional groups, which are polymerized by free radicals and can form a stable SEI film with excellent lithium ion conductivity at the negative electrode. Reduction and decomposition form inorganic components of Li2CO3 and organic components of oligomers and insoluble polymers; C≡C contained in the alkynyl ester group is more prone to bond-breaking polymerization than C=C in the olefinic ester group. The electronegativity of C≡C is stronger than that of C=C and the reaction activity is higher. Since the C≡C group still has unsaturated double bonds after a polymerization reaction, the polymerization reaction can continue until there are no unsaturated bonds in the molecular structure. The inorganic components of Li2CO3 and the organic components of polymers are reduced on the negative electrode side of the electrode to construct a stable SEI film. The benzene ring structure in the compound can form a dense, rigid (benzene ring skeleton) and highly ionic conductive material (N-rich component) SEI film on the surface of the positive electrode of the battery, effectively preventing the oxidation of the positive electrode metal ions on the electrolyte and improving the stability of the electrolyte. In addition, the compound can also replace other additives in the electrolyte to reduce the amount of other additives, and has a dual synergistic effect. Therefore, the electrolyte additive of the present invention can regulate the formation of SEI film, inhibit the generation of lithium dendrites, and thus improve the cycle performance of lithium batteries.

[0009] In some embodiments, the electrolyte additive satisfies at least one of the following:

[0010] (i) the alkenyl ester group includes at least one of C1-C5 alkenyl ester groups;

[0011] (ii) the alkynyl ester group includes at least one of C1-C5 alkynyl ester groups;

[0012] (iii) the number of fluorine atoms in the fluorine-containing group is 1 to 7;

[0013] (iv) The sulfur-containing group includes at least one -SO2- group.

[0014] In some embodiments, the electrolyte additive includes at least one of the following compounds:

[0015]

[0016] In the second aspect of the present invention, the present invention provides a non-aqueous electrolyte, comprising the electrolyte additive of the first aspect. Thus, adding the non-aqueous electrolyte to a battery can significantly improve the cycle performance of the battery.

[0017] In some embodiments, the amount of electrolyte additive added is 0.2-2% based on the non-aqueous electrolyte.

[0018] In some embodiments, the non-aqueous electrolyte further comprises a lithium salt, and the lithium salt satisfies at least one of the following:

[0019] (1) The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium tetrafluoroborate;

[0020] (2) Based on the non-aqueous electrolyte, the amount of lithium salt added is 10 to 25%.

[0021] In some embodiments, the non-aqueous electrolyte further comprises a non-aqueous solvent, and the non-aqueous solvent satisfies at least one of the following:

[0022] (a) the non-aqueous solvent comprises at least one of organic esters, ethers, sulfones and nitriles;

[0023] (b) Based on the non-aqueous electrolyte, the amount of non-aqueous solvent added is 70 to 88%.

[0024] In some embodiments, the non-aqueous electrolyte further comprises other additives, and the other additives satisfy at least one of the following:

[0025] (A) other additives include at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, vinyl bissulfate, propylene sulfate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, methylene disulfonate, triallyl phosphate, tris(trimethylsilyl)phosphate, trimethyl phosphite, triphenyl phosphite, tetramethyl methylene diphosphate, propargyl phosphate, (2-allylphenoxy)trimethylsilane, tris(trimethylsilyl)borate, tripropyl borate, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, lithium difluorophosphate and lithium bis(oxalatoborate);

[0026] (B) Based on the non-aqueous electrolyte, the amount of other additives added is 0.1 to 7%.

[0027] In the third aspect of the present invention, the present invention provides a battery, comprising a positive electrode, a negative electrode, a separator and the non-aqueous electrolyte of the second aspect, so that the battery has excellent cycle performance.

[0028] In some embodiments, the battery is a lithium metal battery or a lithium ion battery.

[0029] Compared with the prior art, the present invention has the following beneficial technical effects:

[0030] (1) The electrolyte additive of the present invention contains a nitro functional group, which can achieve the same technical effect as lithium nitrate (LiNO3) and has a certain solubility, does not affect the conductivity of the electrolyte, has strong compatibility, and can replace lithium nitrate. The nitrate functional group can regulate the formation of the SEI film, so that more nitrogen oxides (LiN x O y and Li3N), thereby significantly improving the stability of the SEI film and the uniformity of lithium deposition and reducing the growth of lithium dendrites.

[0031] (2) The electrolyte additive of the present invention also contains other complex functional groups such as fluorine-containing, sulfur-containing, and benzene rings, which can form SEI films with various structures, thereby improving the cycle performance of lithium batteries and extending battery life.

[0032] (3) The electrolyte additive of the present invention can also replace other additives in the electrolyte to reduce the amount of other additives used, thus having a dual synergistic effect.

[0033] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0034] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0038] In a first aspect of an embodiment of the present invention, the present invention provides an electrolyte additive, comprising at least one of the compounds represented by Formula I and Formula II:

[0039]

[0040] Among them, R 1~8 is at least one of hydrogen, nitro, fluorine-containing group, sulfur-containing group, cyano, isocyano, ene ester group or alkynyl ester group; at least one substituent in formula I is nitro, and at least one substituent in formula II is nitro.

[0041] The electrolyte additive of the present invention comprises at least one of the compounds shown in Formula I and Formula II. On the one hand, the compound has a certain solubility and can form an electrolyte with stable and uniform electrochemical properties; on the other hand, at least one substituent in the compound is a nitro group, which can decompose to produce a LiN-rich electrolyte. x O yThe SEI film of Li3N makes lithium deposition uniform, reduces the consumption rate of active lithium and electrolyte, inhibits the generation of lithium dendrites, and exerts the same technical effect as LiNO3. Other groups in the compound, such as fluorine-containing groups, sulfur-containing groups, cyano groups, isocyano groups, enester groups or alkynyl groups, help the electrolyte to form a solid electrolyte interface film (SEI film) rich in components. For example, compounds containing fluorine groups decompose to produce a SEI film rich in LiF; sulfur-containing groups have stronger reducing properties than carbonates (EC) on the negative electrode side due to the strong electronegativity of sulfur atoms, and can form a stable SEI film with excellent lithium ion conductivity at the interface better than solvents; compounds containing cyano and isocyano groups can remove water and hydrogen fluoride (HF) in the electrolyte, stabilize the electrolyte, and construct an SEI film containing N-based components; enester groups contain C=C double bond functional groups, which are polymerized by free radicals and can form a stable SEI film with excellent lithium ion conductivity at the negative electrode. Reduction and decomposition form inorganic components of Li2CO3 and organic components of oligomers and insoluble polymers; C≡C contained in the alkynyl ester group is more prone to bond-breaking polymerization than C=C in the olefinic ester group. The electronegativity of C≡C is stronger than that of C=C and the reaction activity is higher. Since the C≡C group still has unsaturated double bonds after a polymerization reaction, the polymerization reaction can continue until there are no unsaturated bonds in the molecular structure. The inorganic components of Li2CO3 and the organic components of polymers are reduced on the negative electrode side of the electrode to construct a stable SEI film. The benzene ring structure in the compound can form a dense, rigid (benzene ring skeleton) and highly ionic conductive material (N-rich component) SEI film on the surface of the positive electrode of the battery, effectively preventing the oxidation of the positive electrode metal ions on the electrolyte and improving the stability of the electrolyte. In addition, the compound can also replace other additives in the electrolyte to reduce the amount of other additives, and has a dual synergistic effect. Therefore, the electrolyte additive of the present invention can regulate the formation of SEI film, inhibit the generation of lithium dendrites, and thus improve the cycle performance of lithium batteries.

[0042] In some embodiments of the present invention, the electrolyte additive satisfies at least one of the following:

[0043] (i) the alkenyl ester group includes at least one of C1-C5 alkenyl ester groups;

[0044] (ii) the alkynyl ester group includes at least one of C1-C5 alkynyl ester groups;

[0045] (iii) the number of fluorine atoms in the fluorine-containing group is 1 to 7;

[0046] (iv) The sulfur-containing group includes at least one -SO2- group.

[0047] As an example, the olefinic ester group includes, but is not limited to, at least one of -CH=CH2, -CH2-CH=CH2, -CH2-CH2-CH2-CH=CH2, and -OCOCH=CH2.

[0048] As an example, the alkynyl ester group includes, but is not limited to, at least one of -CH2-C≡C, -CH2-CH2-C≡C, -CH2-CH2-CH2-C≡C, -CH2-COOCH2-C≡C, and -O-COOCH2-C≡C.

[0049] As an example, the fluorine-containing group includes, but is not limited to, at least one of -F, -CF2-CF3, -CF2-CF2-CF3, -CH2CF3, -OCF3, and -OCH2CF3.

[0050] In some embodiments of the present invention, the electrolyte additive includes at least one of the following compounds:

[0051]

[0052]

[0053] The compounds all contain at least one nitro group, which can achieve the same technical effect as lithium nitrate while also having high solubility and strong compatibility. In addition, the compounds also contain at least one of methyl, fluorine-containing groups, sulfur-containing groups, cyano, isocyano, ene ester groups or alkynyl ester groups. These functional groups help the electrolyte to form a SEI film with rich ingredients, thereby significantly improving the stability of the SEI film and the uniformity of lithium deposition, and reducing the growth of lithium dendrites.

[0054] In the second aspect of the present invention, the present invention provides a non-aqueous electrolyte, comprising the electrolyte additive of the first aspect. Thus, adding the non-aqueous electrolyte to a battery can significantly improve the cycle performance of the battery.

[0055] In some embodiments, based on the non-aqueous electrolyte, the amount of the electrolyte additive added is 0.2-2%, and further, the amount of the electrolyte additive added is 0.6-1.2%.

[0056] When the electrolyte additive is added in an amount of 0.2-2%, it can not only stably form a nitrogen- and fluorine-containing SEI film, but also make the lithium deposition morphology on the battery interface dense and flat, without dendrites and fewer holes. Thus, the battery cycle performance can be improved, the battery life can be extended, and the electrochemical performance of the battery will not be adversely affected.

[0057] As an example, the amount of electrolyte additive added is 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc.

[0058] In some embodiments of the present invention, the non-aqueous electrolyte further comprises a lithium salt, and the lithium salt satisfies at least one of the following:

[0059] (1) The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium tetrafluoroborate;

[0060] (2) Based on the non-aqueous electrolyte, the amount of lithium salt added is 10% to 25%, and further, the amount of lithium salt added is 11% to 16%.

[0061] Lithium salts can provide lithium ions after dissociation in the electrolyte. When the addition amount of lithium salts is 10-25%, it can achieve the storage and release of additional energy. At the same time, lithium salts help to form a stable solid electrolyte interface film (SEI film) on the surface of the positive and negative electrode materials of the battery, protecting the electrodes and improving the cycle stability of the battery.

[0062] As an example, the amount of lithium salt added is 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc.

[0063] In some embodiments of the present invention, the non-aqueous electrolyte further comprises a non-aqueous solvent, and the non-aqueous solvent satisfies at least one of the following:

[0064] (a) the non-aqueous solvent comprises at least one of organic esters, ethers, sulfones and nitriles;

[0065] (b) Based on the non-aqueous electrolyte, the amount of the non-aqueous solvent added is 70 to 88%, and further, the amount of the non-aqueous solvent added is 72 to 85%.

[0066] Non-aqueous solvents are mainly used to dissolve lithium salts, transport lithium ions, improve the stability of the electrolyte, and extend the service life of the battery, thereby improving the cycle performance of the battery.

[0067] As an example, the organic esters include at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethyl butyrate, methyl difluoroacetate and ethyl difluoroacetate.

[0068] As an example, the ethers include at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol diethyl ether, and diethylene glycol dimethyl ether.

[0069] As an example, the sulfones include at least one of dimethyl sulfoxide, sulfolane, and dimethyl sulfone.

[0070] As an example, the nitriles include at least one of glutaronitrile, suberonitrile, sebaconitrile, malononitrile, succinonitrile, and adiponitrile.

[0071] As an example, the amount of the non-aqueous solvent added is 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, etc.

[0072] In some embodiments of the present invention, the non-aqueous electrolyte further comprises other additives, and the other additives satisfy at least one of the following conditions:

[0073] (A) other additives include at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, vinyl bissulfate, propylene sulfate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, methylene disulfonate, triallyl phosphate, tris(trimethylsilyl)phosphate, trimethyl phosphite, triphenyl phosphite, tetramethyl methylene diphosphate, propargyl phosphate, (2-allylphenoxy)trimethylsilane, tris(trimethylsilyl)borate, tripropyl borate, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, lithium difluorophosphate and lithium bis(oxalatoborate);

[0074] (B) Based on the non-aqueous electrolyte, the amount of other additives added is 0.1 to 7%.

[0075] Other additives have a coordinated effect with the electrolyte additives of the present invention to improve the stability of the SEI film. For example, compounds containing nitrate groups and fluorine-containing functional groups in their structures can decompose to produce LiN-rich x O y The SEI film of Li3N and LiF can coordinate with the inorganic SEI film of Li2CO3 produced by the decomposition of vinylene carbonate (VC) and Li2SO4 produced by the decomposition of dithiothreitol (DTD), making the lithium deposition uniform, which is beneficial to the cycle stability. At the same time, the interface is dense and flat, and no lithium dendrites are generated. Thus, the interface compatibility between the electrode and the electrolyte is improved, and the cycle performance of the battery is improved.

[0076] As an example, the addition amount of other additives is 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc.

[0077] In a third aspect of the embodiments of the present invention, the present invention provides a battery, comprising a positive electrode, a negative electrode, a separator and the non-aqueous electrolyte of the second aspect, so that the battery has excellent cycle performance.

[0078] In some embodiments of the present invention, the battery is a lithium metal battery or a lithium ion battery.

[0079] Adding the electrolyte additive of the present invention to a lithium metal battery or a lithium ion battery can effectively inhibit the growth of lithium dendrites, thereby improving the cycle performance of the battery and extending the battery life.

[0080] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0081] Embodiment 1:

[0082] (1) Preparation of electrolyte:

[0083] In a glove box filled with argon (water <10ppm, oxygen <10ppm), the solvents ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed at a mass ratio of 3:7. Then, 13% lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solvent, stirred to completely dissolve it, and then electrolyte additives, namely 1% compound 1, 1% vinylene carbonate (VC) and 1% vinyl sulfate (DTD), were added.

[0084] (2) Preparation of batteries:

[0085] Production of positive electrode: LiNi 0.9 Co 0.05 Mn 0.05 O2 (NCM90), conductive agent carbon black (SuperP), adhesive polyvinylidene fluoride (PVDF) and carbon nanotubes (CNT) are mixed evenly at a mass ratio of 95.5:2.5:1.5:0.5 to form a positive electrode slurry for lithium-ion batteries, which is then coated on the positive electrode current collector aluminum foil. After drying at 85°C, cold pressing is performed, and then trimming, cutting, and slitting are performed and then dried at 85°C for 8 hours under vacuum conditions to form a positive electrode sheet for lithium metal batteries.

[0086] The negative electrode sheet is made of 6μm thick copper foil purchased from the market, and a copper-lithium composite strip coated with lithium (lithium thickness is 10μm) on both sides. After trimming, cutting and slitting, it is made into a lithium metal battery negative electrode sheet that meets the requirements.

[0087] The positive electrode sheet, negative electrode sheet and battery separator are then stacked, hot pressed, welded and put into a shell to make a dry battery cell. After the dry battery cell is baked, lithium battery electrolyte is injected to make a battery.

[0088] Embodiment 2:

[0089] The difference between Example 2 and Example 1: the compound in Example 2 is Compound 2.

[0090] Embodiment 3:

[0091] The difference between Example 3 and Example 1: the compound in Example 3 is Compound 3.

[0092] Embodiment 4:

[0093] The difference between Example 4 and Example 1: the compound in Example 4 is Compound 4.

[0094] Embodiment 5:

[0095] The difference between Example 5 and Example 1 is that the electrolyte additives in Example 5 are 1% Compound 5, 1% fluoroethylene carbonate (FEC) and 1% vinylene carbonate (VC).

[0096] Embodiment 6:

[0097] The difference between Example 6 and Example 5: the compound in Example 6 is Compound 6.

[0098] Embodiment 7:

[0099] The difference between Example 7 and Example 5: the compound in Example 7 is Compound 7.

[0100] Embodiment 8:

[0101] The difference between Example 8 and Example 5: the compound in Example 8 is Compound 8.

[0102] Embodiment 9:

[0103] The difference between Example 9 and Example 1: The electrolyte additives in Example 5 are 1% Compound 9, 1% fluoroethylene carbonate (FEC) and 1% diethylene sulfate (DTD).

[0104] Embodiment 10:

[0105] The difference between Example 10 and Example 9: the compound of Example 10 is Compound 10.

[0106] Embodiment 11:

[0107] The difference between Example 11 and Example 9: the compound of Example 11 is Compound 11.

[0108] Embodiment 12:

[0109] The difference between Example 12 and Example 9: the compound of Example 12 is Compound 12.

[0110] Embodiment 13:

[0111] The difference between Example 13 and Example 1 is that the compound in Example 13 is 0.2% of Compound 2.

[0112] Embodiment 14:

[0113] The difference between Example 14 and Example 1 is that the compound in Example 14 is 2% of Compound 2.

[0114] Embodiment 15:

[0115] The difference between Example 15 and Example 5: The compound in Example 15 is 0.2% of Compound 7.

[0116] Embodiment 16:

[0117] The difference between Example 16 and Example 5: the compound in Example 16 is 2% of Compound 7.

[0118] Comparative Example 1:

[0119] The difference between Comparative Example 1 and Example 1 is that the electrolyte additives in Comparative Example 1 are 1% vinylene carbonate (VC), 1% diethylene sulfate (DTD) and 1% fluoroethylene carbonate (FEC).

[0120] Comparative Example 2:

[0121] The difference between Comparative Example 2 and Comparative Example 1 is that Comparative Example 2 adds 0.05% lithium nitrate (LiNO3) to Comparative Example 1.

[0122] Comparative Example 3:

[0123] The difference between Comparative Example 3 and Comparative Example 2 is that the amount of lithium nitrate (LiNO3) added in Comparative Example 3 is 1%.

[0124] Comparative Example 4:

[0125] The difference between Comparative Example 4 and Comparative Example 2 is that the amount of lithium nitrate (LiNO3) added in Comparative Example 4 is 2%.

[0126] Comparative Example 5:

[0127] The difference between Comparative Example 5 and Example 1 is that the added amount of Compound 1 in Comparative Example 5 is 0.1%.

[0128] Comparative Example 6:

[0129] The difference between Comparative Example 6 and Example 1 is that the added amount of Compound 1 in Comparative Example 6 is 2.5%.

[0130] Comparative Example 7:

[0131] The difference between Comparative Example 7 and Example 15: the added amount of Compound 7 in Comparative Example 7 is 0.1%.

[0132] Comparative Example 8:

[0133] The difference between Comparative Example 8 and Example 15: the added amount of Compound 7 in Comparative Example 8 is 2.5%.

[0134] The electrolyte preparation parameters of the above embodiments and comparative examples are shown in Table 1.

[0135] Table 1 Electrolyte preparation parameters for examples and comparative examples

[0136]

[0137]

[0138] Performance Test:

[0139] 1. Test Method

[0140] (a) Electrolyte solubility test:

[0141] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), the prepared electrolyte was tested for turbidity (NTU) using a turbidity meter.

[0142] (b) Interface testing:

[0143] The battery that has been cycled for more than 100 weeks was disassembled in a glove box, rinsed with dimethyl carbonate (DMC), and then isolated from the air and transferred to an electron microscope room to observe the interface state of the battery negative electrode. The interface evaluation criteria are as follows:

[0144] Excellent: dense and flat, no dendrites, few holes;

[0145] Good: relatively dense and flat, with a small amount of dendrites and holes;

[0146] Poor: uneven morphology, with more dendrites, holes and powdery lithium.

[0147] (c) Cycle test:

[0148] The prepared lithium metal battery was placed in a constant temperature room with an ambient temperature of 25°C, charged to 4.2V at a constant current of 0.33C, charged to a cut-off current of 0.05C at a constant current and voltage, and then discharged to 3.0V at a constant current of 0.33C; the discharge capacity was recorded as C1, and the charge and discharge steps were repeated for 300 cycles. The discharge capacity of the nth cycle was C n ;

[0149] The n-th cycle capacity retention rate (%) = (n-th cycle discharge specific capacity / first cycle discharge specific capacity)*100%.

[0150] 2. Test Results

[0151] The performance test results of all embodiments and comparative examples are shown in Table 2.

[0152] Table 2 Performance test results of embodiments and comparative examples

[0153] Group Turbidity (NTU) Cycle 500cls capacity retention rate / % Interface observation Example 1 1.72 84.23% excellent Example 2 1.74 85.08% excellent Example 3 1.7 83.98% excellent Example 4 1.72 85.15% excellent Example 5 1.68 84.28% excellent Example 6 1.7 84.67% excellent Example 7 1.59 86.21% excellent Example 8 1.67 87.08% excellent Example 9 1.6 85.29% excellent Example 10 1.71 86.66% excellent Embodiment 11 1.63 83.97% excellent Example 12 1.57 84.11% excellent Embodiment 13 1.55 83.88% excellent Embodiment 14 1.72 85.4% excellent Embodiment 15 1.69 86.08% excellent Example 16 1.74 85.74% excellent Comparative Example 1 1.31 71.09% Difference Comparative Example 2 55.7 74.69% good Comparative Example 3 150.7 74.22% excellent Comparative Example 4 211.5 75.25% good Comparative Example 5 1.64 77.17% Difference Comparative Example 6 1.75 71.83% excellent Comparative Example 7 1.44 71.26% Difference Comparative Example 8 1.52 70.76% excellent

[0154] From the comparison of the amount of electrolyte additives in Examples 1-16 and Comparative Examples 1-4 or Comparative Examples 5-8 in Table 1, it can be seen that when the compound of the present invention is added to the electrolyte, the usage of other electrolyte additives (electrolyte additive II) can be reduced. Therefore, the compound of the present invention can replace other additives in the electrolyte as an electrolyte additive to reduce the usage of other additives, and has a dual synergistic effect.

[0155] From the turbidity test results in Table 2, it can be seen that the electrolyte additives of the present invention, i.e., the compounds shown in Formula I and Formula II, added to Examples 1-16 and Comparative Examples 5-8 all have high solubility and have no adverse effect on the turbidity of the electrolyte. The turbidity of Comparative Examples 2 to 4 was significantly improved after the addition of LiNO3 compounds, which is due to the large lattice energy of lithium nitrate and low solubility in ester electrolytes. Therefore, it is shown that the electrolyte additive of the present invention has high solubility.

[0156] From the capacity retention and interface observation results in Table 2, it can be seen that Examples 1-16 and Comparative Example 3 have excellent capacity retention and interface state, indicating that the nitro group in the compound of the present invention and 1% LiNO3 can achieve the same technical effect, but have better solubility than LiNO3.

[0157] The molecular structure of the compound of Example 1-4 contains a nitro group and a fluorine-containing group, which can induce the generation of a LiN-rich x O y The SEI film of Li3N and LiF, combined with the SEI film of Li2CO3 and Li2SO4 generated by VC and DTD reduction, can better protect the interface and improve the cycle stability of the battery. When observing the interface under an electron microscope, the lithium deposition morphology is dense and flat, without dendrites and few holes.

[0158] The electrolyte additive in Comparative Example 1 has neither nitro groups nor LiNO3 added, and LiN x O y The SEI interface film of Li3N and LiNO3 is formed, so its cycle stability and interface state are obviously poor. In Comparative Example 2, because the content of the added LiNO3 compound is too low, a stable LiN x O y In Comparative Example 4, due to the high content of LiNO3 added, the solubility of LiNO3 is poor, resulting in increased turbidity of the electrolyte. At the same time, due to the poor solubility, LiN cannot be stably generated. x O yIt blocks the SEI interface film of Li3N and the diaphragm, resulting in poor cycle performance and interface state of the battery.

[0159] In Comparative Examples 5 and 7, due to the low addition amount of the compound, a good and stable nitrogen- and fluorine-containing SEI film could not be formed, so the cycle stability and interface observation results were poor. In Comparative Examples 6 and 8, due to the high addition amount of the compound, the lithium deposition morphology on the interface was dense and flat, without dendrites and fewer holes, but the impedance of the generated SEI film layer was too large, and the cycle performance was significantly deteriorated.

[0160] This indicates that the electrolyte additive of the present invention can effectively inhibit the generation of lithium dendrites and improve the cycle stability of lithium batteries.

[0161] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0162] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An electrolyte additive, characterized in that: Including at least one of the compounds represented by Formula I and Formula II: Among them, R 1~8 is at least one of hydrogen, nitro, fluorine-containing group, sulfur-containing group, cyano, isocyano, ene ester group or alkynyl ester group; at least one substituent in Formula I is nitro, and at least one substituent in Formula II is nitro.

2. The electrolyte additive according to claim 1, characterized in that: The electrolyte additive satisfies at least one of the following: (i) the alkenyl group comprises at least one of C1-C5 alkenyl groups; (ii) the alkynyl ester group includes at least one of C1-C5 alkynyl ester groups; (iii) the number of fluorine atoms in the fluorine-containing group is 1 to 7; (iv) The sulfur-containing group includes at least one -SO2- group.

3. The electrolyte additive according to claim 1 or 2, characterized in that: The electrolyte additive includes at least one of the following compounds:

4. A non-aqueous electrolyte, characterized in that: The electrolyte additive comprises the electrolyte additive according to any one of claims 1 to 3.

5. The non-aqueous electrolyte according to claim 4, characterized in that Based on the non-aqueous electrolyte, the electrolyte additive is added in an amount of 0.2-2%.

6. The non-aqueous electrolyte according to claim 4, characterized in that The non-aqueous electrolyte further comprises a lithium salt, and the lithium salt satisfies at least one of the following: (1) The lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium tetrafluoroborate; (2) Based on the non-aqueous electrolyte, the amount of the lithium salt added is 10-25%.

7. The non-aqueous electrolyte according to claim 4, characterized in that The non-aqueous electrolyte further includes a non-aqueous solvent, and the non-aqueous solvent satisfies at least one of the following: (a) the non-aqueous solvent comprises at least one of organic esters, ethers, sulfones and nitriles; (b) Based on the non-aqueous electrolyte, the amount of the non-aqueous solvent added is 70 to 88%.

8. The non-aqueous electrolyte according to claim 4, characterized in that The non-aqueous electrolyte further comprises other additives, and the other additives satisfy at least one of the following: (A) the other additives include at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, vinyl bissulfate, propylene sulfate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, methylene disulfonate, triallyl phosphate, tris(trimethylsilyl)phosphate, trimethyl phosphite, triphenyl phosphite, tetramethyl methylene diphosphate, propargyl phosphate, (2-allylphenoxy)trimethylsilane, tris(trimethylsilyl)borate, tripropyl borate, 1,3,6-hexanetrinitrile, 1,2-(cyanoethoxy)ethane, lithium difluorophosphate and lithium bis(oxalatoborate); (B) The amount of the other additives added is 0.1 to 7% based on the non-aqueous electrolyte.

9. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the non-aqueous electrolyte according to any one of claims 4 to 8.

10. The battery according to claim 9, characterized in that The battery is a lithium metal battery or a lithium ion battery.